PENGARUH DESAIN PEMBELAJARAN BTQ TERHADAP PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA DI UPTD SDN 1 REJASARI - Syaeful Millah, Ahlan; Dasto; Selamet (As-Sulthan Journal of Education, 2025)
This study aims to determine the effect of the Baca Tulis Al-Qur’an (BTQ) learning design on improving students’ Qur’anic reading skills at UPTD SDN 1 Rejasari. The background of this research is based on the importance of implementing an effective and innovative learning design that aligns with the characteristics of students to achieve optimal BTQ learning outcomes. This study employed a quantitative approach using a quasi-experimental design. The population consisted of all students from grades V, with the sample selected through purposive sampling. The research instruments included a Qur’anic reading ability test and a student response questionnaire toward BTQ learning. Data were analyzed using the t-test to identify differences in average learning outcomes before and after the implementation of the BTQ learning design. The findings revealed a significant effect of the BTQ learning design on improving students’ Qur’anic reading abilities. The implementation of a structured learning design that incorporates interactive media and a gradual approach based on students’ abilities proved effective in enhancing fluency, accuracy of makhraj, and mastery of tajwid in Qur’anic reading. Therefore, it can be concluded that a systematically and contextually developed BTQ learning design contributes positively to improving students’ Qur’anic reading skills at UPTD SDN 1 Rejasari.